Intraoperative pathologic evaluation in thyroid surgery: how much does it contribute to surgical strategy? - Falco, Jorge E.; Verna, Silvina; Dip, Fernando; de la Fuente, Martín; Norte, Matías; Elsner, Boris; Montesinos, Manuel R. (Revista Argentina de Cirugía, 2021)
Background: the role of intraoperative pathologic evaluation (IPE) in thyroid surgery has largely been discussed and it is still controversial. Objective: to estimate the results of IPE in diagnosis of malignancy, its correlation with preoperative fine needle aspiration (FNA) biopsy and permanent pathologic evaluation (PPE), and its contribution to change surgical strategy in thyroid surgery. Materials and methods: retrospective chart review of 773 patients operated on for thyroid disease between January 2014 and December 2015. All patients underwent IPE and PPE; 686 (89%) patients had also preoperative FNA biopsy. Results: IPE resulted benign in 215 patients (27.8%), malignant in 419 (54.2%) and non definitive in 139 (18.0%). When these results were compared with PPE, 19 cases were false negative (8.8%) and 4 false positive (0.95). Considering only definitive results, IPE had sensitivity 95%, specificity 98%, positive predictive value 99%, negative predictive value 91% and accuracy 91%. When IPE was compared with preoperative FNA biopsy, lowest values of sensitivity (44%) corresponded with Bethesda categories III and IV. IPE influenced surgical strategy in 95 patients (12.28%): in 53 (6.8%) hemithyroidectomy changed to total thyroidectomy, in 37 (4.8%) lymph node metastases diagnosis allowed to perform modified neck dissection, and in 5 (0.6%) both situations occurred. Conclusion: IPE had high values of diagnostic utility when compared with PPE. It also correlated with preoperative FNA biopsy, but had less utility in Bethesda categories III and IV. IPE contributed to change surgical technical decision in a subset of patients and avoid a second operation.